Searching for Keynes: An Essay on the Political Economy of Fiscal Policy, with Application to Canada, 1870-2000 - revised version - Stanley L. Winer; J Stephen Ferris (Center for Economic Studies and ifo Institute (CESifo), 2003)
Keynes' General Theory (1936) is arguably one of the most important books of the twentieth century. His ideas for stabilizing the aggregate economy have profoundly influenced economic theory as well as popular opinion about what governments can and should do with respect to the business cycle. On the other hand, whether Keynesian theory has substantially altered the course of public policy remains an open question. In this paper we identify the elements required for any investigation of the impact of Keynes' ideas on policy choices and then conduct our own 'search for Keynes', applying an intertemporal spatial voting framework to study the fiscal history of the Government of Canada from 1870 to 2000. The long time series allows the construction of a counterfactual - one of several essential elements - showing what governments would have planned to do after Keynes', if Keynes' ideas had not in fact been present. Our results suggest that textbook Keynesianism is identifiable in the Canadian data.
Keywords: D72; D78; E12; E62; H30; H60; 330; Keynesianism; spatial voting; permanent versus transitory policy; political equilibrium; liquidity constraints